KEMAMPUAN REPRESENTASI MATEMATIK PADA MATERI SEGI EMPAT SISWA SMP KELAS VII - Euis Nurpadilah; Euis Eti Rohaeti; M Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to determine the ability of mathematical representation of the level of basic ability of students in the rectangular material. The research method used is descriptive. The subject of the research is VII grade SMPN in Karawang. The results of the data analysis showed that the students' upper ability level with the percentage of 83%, had high visual representation ability, medium symbol representation ability, medium verbal representation ability. Students with a middle-level skill level of 72%, have medium visual representation, medium symbol representation ability, and low verbal representation ability. Students with lower base ability level with 50% percentage, medium moderate representation ability, low symbol representation ability, very low verbal representation ability.